2018
DOI: 10.12991/mpj.2018.55
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective effect of cerium oxide nanoparticles on cyclophosphamide-induced nephrotoxicity via anti-apoptotic and antioxidant properties in BALB/c mice

Abstract: Cyclophosphamide [CP], as alkylating agents has side effects such as nephrotoxicity. Cerium oxide nanoparticles [nanoceria; NC], as an antioxidant, are effective at reduction oxidative stress. This study evaluated the protective effect of nanoceria in nephrotoxicity induced CP. 32 BALB/c mice were randomly divided into four equal groups. Control, NC, CP and NC+CP. NC and CP injected intraperitoneally respectively in dose of 100 μg/kg for 3 days and 200 mg/kg single dose on 3th day of study. Two days after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
(54 reference statements)
1
11
1
Order By: Relevance
“…The content of the glutathione (GSH) in the ovary gland was calculated by spectrophotometer with 5,5 0 -dithiobis-2-nitrobenzoic acid (DTNB) as an indicator at 412 nm and expressed as μmol/gr tissue. 19…”
Section: Histochemical Assaysmentioning
confidence: 99%
“…The content of the glutathione (GSH) in the ovary gland was calculated by spectrophotometer with 5,5 0 -dithiobis-2-nitrobenzoic acid (DTNB) as an indicator at 412 nm and expressed as μmol/gr tissue. 19…”
Section: Histochemical Assaysmentioning
confidence: 99%
“…Lead exposure may significantly improve endothelial NO production [8]. Nitric acid can cause damage to proteins, lipids, and deoxyribonucleic acid (DNA) either directly or after interaction with superoxide [31]. e administration of methanol extract of okra pods showed the depletion of NO level and restored it to normal.…”
Section: E Effect Of Methanol Extract Of Okra Pods On No Levelmentioning
confidence: 99%
“…This element along with a reduction in the accumulation of reactive oxygen species (ROS) inhibits apoptosis due to antioxidant effects (12). NC, as one of the most important classes of nanomaterial and with the redox capability, have antioxidant properties that scavenge free radicals (13). The protective effect of NC in in vitro and in vivo studies has been demonstrated (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…NC, as one of the most important classes of nanomaterial and with the redox capability, have antioxidant properties that scavenge free radicals (13). The protective effect of NC in in vitro and in vivo studies has been demonstrated (13,14). However, this effect on hepatotoxicity induced by CP has been not established.…”
Section: Introductionmentioning
confidence: 99%